A permanent fault identification method for single-pole grounding fault of overhead transmission lines in VSC-HVDC grid based on fault line voltage. (May 2020) - Li, Botong; Cui, Hanqing; Li, Bin; Wen, Weijie; Dai, Dongkang
Highlights: The permanent fault identification is based on the fault line voltage. The current of the fault line is small during the permanent fault identification. Accuracy of method is not affected by line length, fault resistance, fault position. Abstract: In this paper, a permanent fault identification method for single-pole grounding fault of overhead transmission lines in VSC-HVDC grid based on fault line voltage is proposed. First, the working principle of the hybrid direct breaker circuit breaker ( DCCB) and the discharge process of the internal capacitor of the hybrid DCCB are analyzed. Then, the transient processes of the fault line voltage under the conditions of permanent fault and transient fault are analyzed after reclosing the isolation switch of the DCCB on one side of the fault line. According to the difference of the fault line voltage under the conditions of permanent fault and transient fault, a permanent fault identification method for single-pole grounding fault of overhead transmission lines is proposed. The process of the identification will not affect the operating state of each converter in VSC-HVDC grid and it will not cause another fault impact to the system. Finally, a model of four-terminal VSC-HVDC system based on the modular multilevel converter (MMC) is built in PSCAD and the simulation results verify the feasibility and accuracy of this method.